THE APPLICATION OF PROBLEM-BASED LEARNING MODELS TO IMPROVE MATHEMATICS LEARNING OUTCOMES FOR STUDENTS OF CLASS XII IPA 6 SMA NEGERI 4 PEKANBARU - Citra Aries (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2021)
This classroom action research aims to improve the learning process and improve mathematics learning outcomes by applying problem-solving strategies through problem-based learning. The subjects of this study were students of class XII IPA 6 SMA Negeri 4 Pekanbaru, totaling 38 students with academic ability levels heterogeneous. This study consisted of two cycles consisting of four stages, namely planning, implementation, observation, and reflection. Data collection was carried out through observations of teacher and students activities and learning outcomes tests in daily tests. There is an improvement towards a better direction in the learning process after problem-solving strategies through problem-based learning. This can be seen in students who participate actively and are more responsible in the learning process, such as discussing, presenting, expressing opinions, and asking questions to provide a learning conclusion. The number of students who achieved the KKM on the basic score, daily test I (first cycle), daily test II (second cycle) was 47,36%, 65,78%, and 92,10%, respectively. The percentage of KKM achievement also shows an increase from before to after the action, so that it can be said that student learning outcomes also increase. The results of this study indicate that the application of problem solving strategies through problem-based learning can improve the learning process and improve mathematics learning outcomes for students of grade XII science 6 SMA Negeri 4 Pekanbaru.